2016
DOI: 10.1038/ncomms10622
|View full text |Cite
|
Sign up to set email alerts
|

Cellular delivery and photochemical release of a caged inositol-pyrophosphate induces PH-domain translocation in cellulo

Abstract: Inositol pyrophosphates, such as diphospho-myo-inositol pentakisphosphates (InsP7), are an important family of signalling molecules, implicated in many cellular processes and therapeutic indications including insulin secretion, glucose homeostasis and weight gain. To understand their cellular functions, chemical tools such as photocaged analogues for their real-time modulation in cells are required. Here we describe a concise, modular synthesis of InsP7 and caged InsP7. The caged molecule is stable and release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 57 publications
2
92
0
Order By: Relevance
“…Kinase and Phosphatase Assays-PPIP5K kinase activities were routinely measured at 37°C in 1-2-h incubations comprising 100 l of assay buffer containing 1 mM Na 2 EDTA, 50 mM KCl, 20 mM HEPES (pH 7.2), 7 mM MgCl 2 , 5 mM ATP, 0.5 mg/ml BSA, and either 1 M InsP 6 (Calbiochem) or 1 M chemically synthesized 5-InsP 7 (47). PPIP5K phosphatase activities were measured at 37°C in 30-min incubations comprising 100 l of assay buffer containing 1 mM Na 2 EDTA, 50 mM KCl, 20 mM HEPES (pH 7.2), 2 mM MgCl 2 , 0.5 mg/ml BSA, and either 1 or 0.05 M chemically synthesized 1-InsP 7 (48) or InsP 8 (30).…”
Section: Methodsmentioning
confidence: 99%
“…Kinase and Phosphatase Assays-PPIP5K kinase activities were routinely measured at 37°C in 1-2-h incubations comprising 100 l of assay buffer containing 1 mM Na 2 EDTA, 50 mM KCl, 20 mM HEPES (pH 7.2), 7 mM MgCl 2 , 5 mM ATP, 0.5 mg/ml BSA, and either 1 M InsP 6 (Calbiochem) or 1 M chemically synthesized 5-InsP 7 (47). PPIP5K phosphatase activities were measured at 37°C in 30-min incubations comprising 100 l of assay buffer containing 1 mM Na 2 EDTA, 50 mM KCl, 20 mM HEPES (pH 7.2), 2 mM MgCl 2 , 0.5 mg/ml BSA, and either 1 or 0.05 M chemically synthesized 1-InsP 7 (48) or InsP 8 (30).…”
Section: Methodsmentioning
confidence: 99%
“…50 μl. Next, each sample was spiked with 1 nmol of InsP 6 (Calbiochem), and 1 nmol each of chemically synthesized 1-InsP 7 [22], 5-InsP 7 [23], and InsP 8 [24]. For some experiments (as indicated below), 20 nmol 5-InsP 7 were added.…”
Section: Methodsmentioning
confidence: 99%
“…78 A recent study revealed that chemically synthesized 5-IP 7 released into mammalian cells is able to induce translocation of AKT from the plasma membrane to the cytoplasm. 79 It has been shown that AKT and other PH domains bind 5-IP 7 and IP 6 with higher affinity as compared with 1-IP 7 or IP 8 . 41 This study also suggested that PI(3,4,5)P 3 dependent recruitment of PPIP5K1 to the plasma membrane would deplete subplasmalemmal 5-IP 7 and IP 6 by using them as substrates, thus providing positive feedback to PI(3,4,5)P 3 binding by PH domains at the plasma membrane.…”
Section: Plasma Membranementioning
confidence: 99%
“…78,79,[126][127][128][129] Highly pure PP-IPs with β-phosphate moieties at specific carbon atoms have been synthesized by these groups, including non-hydrolysable analogues that are stable in cells and can bind target proteins but not pyrophosphorylate them. 47,78,130 A system for intracellular delivery and photouncaging of chemically synthesized PP-IPs has recently been developed, 79 which promises to open up new methods to study the functions of these molecules in different subcellular compartments. The use of IP 7 as an affinity reagent revealed two different classes of interacting proteins, depending on the absence or presence of the divalent cation Mg 2+ during the interaction, representing IP 7 binding or pyrophosphorylation targets respectively.…”
Section: Perspective On the Futurementioning
confidence: 99%